Konsep Diri dan Komunikasi Interpersonal Pada Siswa SMP - Tiwi Fatimah; Abdul Amin (Academic Journal of Psychology and Counseling, 2022)
Humans are social creatures and in everyday life always interact with other people. Therefore, communication skills are very important to build good relationships with other people around them. The purpose of this study was to determine the relationship between self-concept and interpersonal communication. The population of this study were students of SMPN 2 Tutur. The sample used was 98 respondents who were taken using quota sampling technique. Collecting data using interpersonal communication scale and self-concept scale. The data obtained were then analyzed using correlation analysis. The results of the data analysis show the correlation coefficient is 0.581. The result show that there is a relationship between self-concept and interpersonal communication, where when a person's self-concept is good, the interpersonal communication will be better. Conversely, when a person's self-concept is bad, the interpersonal communication will be worse.